FACTORS INFLUENCING EDUCATION QUALITY MANAGEMENT: CONTINUOUS IMPROVEMENT, LEADERSHIP STYLE AND CUSTOMER SATISFACTIO (LITERATURE REVIEW MPI) - Muhammad Alfian; Hapzi Ali; Kemas Imron Rosadi; Fitriyani Fitriyani (Dinasti International Journal of Management Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence education quality management, namely: continuous improvement, leadership style, and customer satisfaction, a literature study of Islamic education management. The purpose of writing this article is to build a hypothesis about the influence between variables that can be used in further research. The results of this literature review article are: 1) Continuous Improvement has an effect on Education Quality Management; 2) Leadership Style has an effect on Education Quality Management; and 3) Customer Satisfaction has an effect on Education Quality Management.